2007
DOI: 10.1136/ard.2006.067975
|View full text |Cite
|
Sign up to set email alerts
|

Predicting poor functional outcome in community-dwelling older adults with knee pain: prognostic value of generic indicators

Abstract: Background: In longitudinal studies across a range of regional musculoskeletal pain syndromes, certain prognostic factors consistently emerge. They are ''generic'' in the sense that they appear to apply regardless of the particular anatomical site or underlying cause of the pain. Objective: To investigate the value of generic indicators of poor functional outcome for knee pain and osteoarthritis in the community. Methods: We conducted a population-based cohort study of adults aged >50 years with knee pain as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 35 publications
(34 reference statements)
7
77
1
Order By: Relevance
“…This is the first study that is primarily aimed at examining the interrelations between BMI, depressed mood, knee pain and activity limitations in knee OA. Five earlier studies examined these interrelations in the context of a larger study on determinants of pain and activity limitations [9,12,[17][18][19]. The results of two of these five studies were in agreement with our results [12,17].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is the first study that is primarily aimed at examining the interrelations between BMI, depressed mood, knee pain and activity limitations in knee OA. Five earlier studies examined these interrelations in the context of a larger study on determinants of pain and activity limitations [9,12,[17][18][19]. The results of two of these five studies were in agreement with our results [12,17].…”
Section: Discussionsupporting
confidence: 82%
“…The results of two of these five studies were in agreement with our results [12,17]. Three studies did not find independent associations between BMI, depressed mood, and pain and activity limitations [9,18,19]. However, the latter studies found that BMI and helplessness [18] or anxiety [9] (psychological concepts closely related to depressed mood) were independently associated with pain or activity limitations.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Associations between activity limitations in knee and/or hip OA and ethnicity (11,34,35), multiplesite joint pain (36,37), morning stiffness (38), comorbidity count (5,39), BMI (8), impaired hip flexion (33), bodily pain (8), general health perception (6), and the pain coping strategy transformation (40) have been identified previously in established OA. Furthermore, the results of the present study confirm earlier observations that radiographic status is not closely associated with physical function in patients with knee or hip OA (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%